2019
DOI: 10.3389/fimmu.2019.01508
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Down-Regulate Gene Expression of Intervertebral Disc Degenerative Markers Under a Pro-inflammatory Microenvironment

Abstract: Low back pain is a highly prevalent clinical problem and intervertebral disc (IVD) degeneration is now accepted as the major pathophysiological mechanism responsible for this condition. Accumulating evidence suggests that inflammation plays a crucial role in the progression of human IVD degeneration, with macrophages being pointed as the key immune cell players in this process since their infiltration in degenerated IVD samples has been extensively demonstrated. Since they are highly plastic, macrophages can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…By co-culture of autologous or allogeneic peripheral blood mononuclear cells and NP cells, Stich et al found elevated immune cell proliferation levels in 3Dcultures than 2D-cultures, and a general trend to higher responses for NP cells from severely degenerated IVD tissue [47], indicating that autoimmune response could vary depending on different cell cultures and degeneration degrees. More recently, Silva et al established a model of IVD organ culture, found that human macrophages could be polarized toward a more pro-inflammatory profile by degenerated IVD tissue, and interfere with IVD ECM remodeling by downregulating aggrecan and collagen II gene expression in the presence of IL-1β [48]. These findings showed that with the breakdown of the BNB, the exposed NP tissue could induce autoimmune response, which stimulates both immunocytes activation and inflammatory factors infiltration ( Figure 2B).…”
Section: Auto-immune Response Of the Npmentioning
confidence: 99%
See 1 more Smart Citation
“…By co-culture of autologous or allogeneic peripheral blood mononuclear cells and NP cells, Stich et al found elevated immune cell proliferation levels in 3Dcultures than 2D-cultures, and a general trend to higher responses for NP cells from severely degenerated IVD tissue [47], indicating that autoimmune response could vary depending on different cell cultures and degeneration degrees. More recently, Silva et al established a model of IVD organ culture, found that human macrophages could be polarized toward a more pro-inflammatory profile by degenerated IVD tissue, and interfere with IVD ECM remodeling by downregulating aggrecan and collagen II gene expression in the presence of IL-1β [48]. These findings showed that with the breakdown of the BNB, the exposed NP tissue could induce autoimmune response, which stimulates both immunocytes activation and inflammatory factors infiltration ( Figure 2B).…”
Section: Auto-immune Response Of the Npmentioning
confidence: 99%
“…Also, in a co-cultures system, Yang et al showed that AF or NP cells exposed to macrophages upregulated the expression of pro-inflammatory mediators [50]. As for the ECM, studies have found that immunocytes could interfere with IVD ECM remodeling and downregulate aggrecan and collagen II expression [48]. In addition, the expression of matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs) were increased in IVD with autoimmune reaction, causing the degradation of ECM [51,52].…”
Section: Auto-immune Response Of the Npmentioning
confidence: 99%
“…IVDs culture under proinflammatory conditions (puncture + IL-1β) with macrophages Macrophages interfere in the IVD ECM remodeling and exhibit a more-proinflammatory profile in contact with IVD degenerated tissue. [143] vivo processes, [116b] low oxygenation and nutrition, [118] or proinflammatory cues. [116c] Ex vivo studies use a variety of tissue sources, including human, bovine, sheep, rabbit, rat, and mouse, among others and are commonly safe and easy to manipulate.…”
Section: Ex Vivo Models-increased Complexity In 3dmentioning
confidence: 99%
“…As the stage of degeneration progresses, the production of pro-inflammatory molecules, including tumor necrosis factor (TNF)-α, interferon gamma (IFN-γ), and interleukin (IL-1β, IL-6, IL-1α and IL-2) increases [ 5 ]. These molecules can be produced by both IVD cells and immune cells, such as macrophages [ 6 ], and are known to be associated with discogenic back pain [ 6 ]. IVD degeneration is characterized by the loss of IVD cells and extracellular matrix (ECM) such as aggrecan and collagen type II, with the upregulation of matrix metalloproteinases (MMPs) and inflammatory mediators leading to progressive and irreversible damage of IVD structure [ 1 , 3 , 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These molecules can be produced by both IVD cells and immune cells, such as macrophages [ 6 ], and are known to be associated with discogenic back pain [ 6 ]. IVD degeneration is characterized by the loss of IVD cells and extracellular matrix (ECM) such as aggrecan and collagen type II, with the upregulation of matrix metalloproteinases (MMPs) and inflammatory mediators leading to progressive and irreversible damage of IVD structure [ 1 , 3 , 4 , 6 , 7 , 8 ]. Eventually, IVD degeneration can lead to the onset of additional spinal conditions, including disc herniation, spinal stenosis, facet joint osteoarthritis, and spondylolisthesis [ 1 , 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%